(untitled) (Discourse of Law and Administration, 2021)
The article deals with the issue of the importance of the defense counsel’s closing speech in the criminal trial. The analysis of the issue of the composition of the defence speech is conducted in the perspective of rhetorical invention and the doctrine of staseis. The author observes that the phase of final statements, which is a separate stage of the trial, may be perceived as a fundamental guarantee of the right to be heard before a court, which is a constituent element of the principle of the right to a court and the principle of a fair trial, anchored in the constitutional plane in Article 45 paragraph 1 of the Polish Constitution and in the Convention area in Article 6 paragraph 1 of the ECHR. The considerations lead to the conclusion that through the final voices (speeches) of the parties and their representatives representing the opposing procedural interests, the essence of the procedural dispute and the legal dispute between the prosecutor and the accused becomes most evident. This dispute is the content of the criminal proceedings until the closing of the trial, after which there is already a judicial decision on the subject of the trial that is binding on the parties.